Expression of TLR-7, MyD88, NF-kB, and INF-α in B Lymphocytes of Mayan Women with Systemic Lupus Erythematosus in Mexico - Pacheco, Guillermo Valencia; Novelo Noh, Irene B.; Velasco Cárdenas, Rubí M.-H.; Angulo Ramírez, Angélica V.; López Villanueva, Ricardo F.; Quintal Ortiz, Irma G.; Alonso Salomón, Ligia G.; Ruz, Norma Pavía; Rivero Cárdenas, Nubia A. (Frontiers in Immunology, 2016)
Background Systemic lupus erythematosus (SLE) is a chronic inflammatory autoimmune disease involving multiple organs. It is currently accepted that several genetic, environmental, and hormonal factors are contributing to its development. Innate immunity may have a great influence in autoimmunity through Toll-like receptors. TLR-7 recognizing single-strand RNA has been involved in SLE. Its activation induces intracellular signal with attraction of MyD88 and NF-kBp65, leading to IFN-α synthesis which correlate with disease activity. Objective To assess the expression of TLR-7, MyD88, and NF-kBp65 in B lymphocytes of Mayan women with SLE. Methods One hundred patients with SLE and 100 healthy controls, all of them Mayan women, were included. TLR-7 was analyzed on B and T lymphocytes, and MyD88 and NF-kB only in B lymphocytes. Serum INF-α level was evaluated by ELISA. Results Significant expression (p < 0.0001) of TLR-7 in B and T lymphocytes and serum IFN-α increased (p = 0.034) was observed in patients. MyD88 and NF-kBp65 were also increased in B lymphocytes of patients. TLR-7 and NF-kBp65 expression correlated, but no correlation with INF-α and disease activity was detected. Conclusion Data support the role of TLR-7 and signal proteins in the pathogenesis of SLE in the Mayan population of Yucatán.